Dahuang Mudan decoction repairs intestinal barrier in chronic colitic mice by regulating the function of ILC3. (5th December 2022) - Huang, Shaowei; Wang, Xiaojing; Xie, Xueqian; Su, Yulin; Pan, Zengfeng; Li, Yanyang; Liang, Junjie; Zhang, Meiling; Pan, Simin; Xu, Bo; Li, Linzhu; Chen, Jinyan; et al.
Abstract: Ethnopharmacological relevance: Dahuang Mudan decoction (DMD) is a classic prescription for treating intestinal carbuncle from Zhang Zhongjing's "Essentials of the Golden Chamber" in the Han Dynasty. Recent studies also prove that DMD has a therapeutic effect on ulcerative colitis (UC), but its mechanism is still unclear. Aim of study: In this study, we aim to assess the therapeutic effect of DMD on DSS-induced chronic colitis in mice and deeply expound its underlying regulative mechanism. Materials and methods: The efficacy of DMD on mice with 2% DSS-induced chronic colitis was examined by changes in mouse body weight, DAI score, colon length changes, peripheral blood white blood cells (WBC) and red blood cells (RBC) counts, and hemoglobin (HGB) content, using mesalazine as a positive control. A small animal imaging system observed the FITC-Dextran fluorescence distribution in mice, and the contents of IL-22 and IL-17A in colon tissue homogenate supernatant and LPS in peripheral blood were detected by ELISA. Fluorescence in situ molecular hybridization and bacterial culture were used to investigate bacterial infiltration in intestinal mucosa and bacterial translocation in mesenteric lymph nodes and spleen. Mice immune function was further evaluated by analyzing the changes in spleen index, thymus index, and the ratio of peripheral blood granulocytes, monocytes, and lymphocytes. Meanwhile, the proportion of NCR + group 3 innate lymphoid cells (ILC3), NCR - ILC3, and IL-22 + ILC3 in colonic lamina propria lymphocytes of mice was detected by flow cytometry. The contents of effectors IL-22, IL-17A, and GM-CSF were detected by RT-PCR. We use cell scratching to determine the effect of DMD conditioned medium on the migration of Caco-2 cells by establishing an in vitro model of MNK-3 conditioned medium (CM) intervening Caco-2 cells. RT-PCR and WB detect the expression of tight junction ZO-1, Occludin, and Claudin-1. Results: DMD restored the body weight, colon length, peripheral blood RBC numbers, and HGB content of chronic colitis mice and reduced peripheral blood WBC and colon inflammatory cell infiltration. Moreover, DMD decreased LPS content in serum, bacterial infiltration of colonic mucosa, and bacterial translocation in spleen and mesenteric lymph nodes. Simultaneously, DMD intensified the expression of ZO-1, Occludin, and Claudin-1, the ratio of NCR + ILC3 and IL-22 + ILC3, and decreased the proportion of NCR - ILC3. In vitro studies also confirmed that the conditioned medium of DMD promoted the migration of Caco-2 cells and the expression of tight junction proteins. Conclusion: Our results confirm that DMD improves inflammation and restores intestinal epithelial function in mice with chronic colitis, and the mechanism may be related to regulating ILC3 function. Graphical abstract: Image 1